STUDY OF DIFFERENT WINGLET CONFIGURATION IN CEILING FAN TO IMPROVE THE AIR FLOW IN CUBIC ROOM - KARTHIKEYAN, ARTHANARI (MECHANICAL ; Jurnal Ilmiah Teknik Mesin, 2025)
Winglet attachment is reducing the induced drag in aircraft; similar concept is tried in ceiling fan, in order to reduce the tip vortices which increase the fan speed and airflow and reduce the electricity consumption. Various shape of winglet attachment such as blend edge, sharp edge, wedge shape, triangle. The air flow was experimentally measured at various locations in various speeds and results were finally discussed. There is a considerable improvement in airflow as compared to without attachment of winglet